2012
DOI: 10.1097/mao.0b013e31824b774c
|View full text |Cite
|
Sign up to set email alerts
|

Is it the Middle Ear Disease or the Reconstruction Material That Determines the Functional Outcome in Ossicular Chain Reconstruction?

Abstract: The results of this study revealed that none of the reconstruction materials or specific techniques have a superiority in the functional outcomes in patients from the same middle ear risk group. We conclude that the success of ossiculoplasty is highly correlated with the pathophysiological status of the middle ear and is independent of the type of replacement material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 21 publications
0
13
0
2
Order By: Relevance
“…In this study the mean preoperative PTA average was 44. and air-conduction improvement (p<0.001 for both) were statistically significant in the mild-and moderate-risk groups, whereas those changes were found to be insignificant in the 9 severe-risk group .…”
Section: Discussionmentioning
confidence: 72%
“…In this study the mean preoperative PTA average was 44. and air-conduction improvement (p<0.001 for both) were statistically significant in the mild-and moderate-risk groups, whereas those changes were found to be insignificant in the 9 severe-risk group .…”
Section: Discussionmentioning
confidence: 72%
“…The two indexes similarly report middle ear factors such as otorrhea, status of the mucosa, status of the ossicles, and stage procedure status (revision or first-stage procedure). Based on the MERI, Demir et al (10) have shown that the success rate is highly correlated with the pathophysiologic status of the middle ear independently from the type of replacement material. Indeed, different types of prosthesis for ossiculoplasty were compared, and no obvious differences were found by most studies (11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…This is certainly an unanswered question that is worthy of further research and scrutiny, yet recent data suggest that the middle ear status may be the most important determinant of ossiculoplasty success (25). It is the authors' hope that future efforts in this realm will take note of the general investigational method that is outlined in this report, involving an attempt to compare predicted versus actual hearing outcomes and to frame results based on middle ear risk factors (25). We believe investigators should use the OOPS or one of the other similar published middle ear risk indices for this purpose (15,16,18,19).…”
Section: Discussionmentioning
confidence: 96%